MT2 receptor mediates melatonin-induced thermogenic program in human myoblasts: insights for circadian syndrome and diabesity treatment - Diego Salagre; Juan Sanjuán‐Hidalgo; Ehab Kotb Elmahallawy; Ehab Kotb Elmahallawy; Pedro P. Medina; Ahmad Agil (Frontiers in Pharmacology)
BackgroundMelatonin is crucial for regulating circadian rhythms. Previous studies have demonstrated its ability to improve metabolic disorders, including obesity and associated diabetes (diabesity), in addition to its antioxidant, anti-inflammatory and anti-apoptotic properties. Recently, melatonin was shown to reduce obesity by increasing skeletal muscle (SKM) energy expenditure through non-shivering thermogenesis (NST). Small interfering RNAs (siRNAs) are powerful tools for inhibiting gene expression, enabling the analysis of gene functions and roles in molecular pathway activation. This study aimed to identify the receptor mediating melatonin’s pharmacological actions in SKM NST.MethodsBioinformatics and protein-protein interaction (PPI) analyses were conducted. To examine the role of the melatonin receptor 2 (MT2) encoded by MTNR1B, we cultured human primary myoblasts and then silenced MTNR1B using siRNA transfection for 72 h, followed by 1 mM melatonin treatment for 24 h. Gene and protein expression were analyzed using semi-quantitative reverse transcriptase PCR and Western blotting respectively.ResultsPPI analysis revealed MTNR1B’s strong association with diabetes, obesity, cancer, and circadian rhythm disorders, collectively known as circadian syndrome, and MTNR1B’s close interaction with thermogenic genes (UCP1, PPARG, and PPARGC1A). Silencing MTNR1B reduced the gene expression and inhibited the melatonin-induced upregulation of MT2 and NST-related proteins. Melatonin increased SERCA1/2, SLN, and Ca2+-dependent thermogenic pathway activation; however, these effects were abolished following MTNR1B knockdown.ConclusionOur findings confirm that MT2 plays a key role in melatonin-driven SERCA-SLN uncoupling and the activation of the thermogenic program in SKM via the CaMKII/AMPK/PGC1α pathway upregulation. This study provides new insights into the molecular mechanisms underlying melatonin’s effects on thermogenesis and suggests potential melatonin-based therapeutic strategies against diabesity.